Stimulation of matrix formation in rabbit chondrocyte cultures by ascorbate. 1. Effect of ascorbate analogs and beta-aminopropionitrile - Wright, Jr, G C; Wei, X Q; McDevitt, C A; Lane, B P; Sokoloff, L (Journal of orthopaedic research, 1988)
The most consistent effects of 0.2 mM L-ascorbate on monolayer cultures of rabbit articular chondrocytes were a diversion of incorporated radiosulfate into a pericellular matrix and enhancement of cell proliferation. Only with certain batches of fetal bovine serum (FBS) was there a cell-for-cell increase of proteoglycan synthesis. These actions increased as the cell inoculum rose from 0.5 to 2 x 10(5) cells/T25 flask. Maximal effects of ascorbate and D-isoascorbate were found over a range of 0.05-0.2 mM. L-Dehydroascorbic acid was less effective than either, and no stimulatory action was exerted by L-cysteine, glutathione, dithiothreitol, methylene blue, or phenazine methosulfate. Ascorbate increased the hypro:pro ratio of newly synthesized proteins. beta-Aminopropionitrile (1 mM) reduced the proportion of [3H]hydroxyproline and [35S]O4-proteoglycans in the ascorbate-supplemented matrix 31 and 7%, respectively. In corresponding electronmicrographs, the number of pericellular filaments was reduced. We conclude: (a) Ascorbate has a general anabolic effect on chondrocytes in culture and enhances matrix assembly through mechanisms other than its redox function; (b) deposition of proteoglycans in the matrix is not simply the result of mechanical entrapment by allysine- or hydroxyallysine-derived cross-linking of collagen; and (c) contradictory reports on the subject result from variations in the serum employed, inoculum density, and concentration of ascorbate.